The South, the suburbs, and the Vatican too: explaining partisan change among Catholics - Ryan, John Barry; Milazzo, Caitlin (Springer, 2015)
This paper explains changes in partisanship among Catholics in the last quarter of the 20th Century using a theory of partisan change centered on the contexts in which Catholics lived. Catholics were part of the post-New Deal Democratic coalition, but they have become a swing demographic group. We argue that these changes in partisanship are best explained by changes in elite messages that are filtered through an individual’s social network. Those Catholics who lived or moved into the increasingly Republican suburbs and South were the Catholics who were most likely to adopt a non-Democratic partisan identity. Changes in context better explain Catholic partisanship than party abortion policy post Roe v. Wade or ideological sorting. We demonstrate evidence in support of our argument using the ANES cumulative file from 1972 through 2000.